ARE WEALTHY REGIONS ALSO ENTREPRENEURIAL? THE CASE OF INDONESIA - Widiastuti, Wini (Journal of Regional and City Planning, 2020)
The relationship between economic development and entrepreneurship is complex and dynamic, especially at the regional level. Entrepreneurship can emerge in both wealthy and poorer regions, triggered either by necessity or opportunity. This article performed a spatial analysis of Indonesian data to identify the regional patterns of entrepreneurial activity and to test whether wealthy regions are more entrepreneurial than poorer regions, considering both supply and demand factors. Spatial regression analysis using GeoDa was performed to examine the extent to which regional conditions affect different types of enterprises (formal and informal). The results show that wealthy regions are more entrepreneurial with regard to informal businesses but not formal businesses. The supply side analysis confirmed that being unemployment stimulates individuals to become entrepreneurs (necessity-based entrepreneurship). Meanwhile, the demand side analysis confirmed that the size of market demand positively influences entrepreneurship (opportunity-based entrepreneurship).Abstrak. Hubungan antara pengembangan ekonomi dan kewirausahaan adalah kompleks dan dinamis terutama pada tingkat regional. Kewirausahaan dapat muncul baik di daerah kaya maupun miskin karena dipicu oleh faktor kebutuhan atau peluang. Artikel ini melakukan analisis spasial pada data Indonesia untuk mengidentifikasi pola regional kegiatan kewirausahaan dan untuk menguji apakah daerah kaya lebih berjiwa wirausaha daripada yang lebih miskin dengan mempertimbangkan faktor penawaran dan permintaan. Analisis regresi spasial menggunakan Geoda dilakukan untuk memeriksa sejauh mana kondisi regional mempengaruhi berbagai jenis bisnis, perusahaan formal dan informal. Hasilnya menunjukkan bahwa daerah kaya lebih berwirausaha dalam hal perusahaan informal tetapi tidak untuk perusahaan formal. Analisis sisi penawaran menegaskan bahwa menganggur merangsang individu untuk menjadi wirausaha yang merupakan kewirausahaan berbasis kebutuhan. Sementara itu, analisis sisi permintaan menegaskan bahwa ukuran permintaan pasar secara positif mempengaruhi kewirausahaan yaitu kewirausahaan berbasis peluang.Kata kunci. Kewirausahaan, tingkat permulaan, pembangunan ekonomi wilayah, negara-negara berkembang.